Nghiên cứu xử lý số sóng hài bậc 3, chế tạo relay bảo vệ chạm đất máy phát điện trong vùng công suất thấp - giới, nguyễn (Vietnam Journal of Science and Technology, 2014)
This article shows distribution model of the third harmonic of voltage in the winding of three phase salient pole rotor alternating-current synchronous  generator (DMHW).The base on that to put forward a mathematical formula for formalize to process for physically, which occurs on winding of  the generator by the third harmonic of voltage  and called  be Winding Characteristic Equation and it is abbreviated to WCE. These  many different methods are based on WCE to protect the stator winding in the case of ground faults in high resistance grounded synchronous generator above. Using third harmonic of voltage to protect winding with standard ANSI 27/59NT 3rd harm by filter harmonic wave voltage measured at terminal or  neutral. In the method, function of third harmonic of voltage  has variable to be real power. But WCE could reject the variable by to algebraic subtract the third harmonic of  voltage of the neutral transformer from the third harmonic of voltage of the third harmonic terminal transformer. It is possible to infer the third harmonic electromotive force(e3rd) from per unit length of the winding is equal, because the flux magnet of third harmonic wave swept them is similar in the magnetic field intensity. On the other hand, according to our calculations, sum of e3rd on the stator winding equal zero. Base of  that, quotient of the third harmonic voltage at terminal and neutral  exactly reflects the ratio of the area on the  stator  winding  and the  stator winding  length , where occurs ground fault  position. For this reason, we have proposed a protection formula, which it is non-dimensional. Reality, with above principle, we have made a new equipment which is aimed to obtain a 100% protection of the stator winding in the case of ground faults on every power range [-40MVA; 110MVA] of the generator operation. The components of the equipment have origin of Siemens and Russian. And it has fitted up at the our Company, in October , 2012.